FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN SELF ASSESMENT SYSTEM (SURVEY PADA WAJIB PAJAK ORANG PRIBADI DI KOTA SEMARANG) - Haq, Maulana Syaiful; Muid, Dul (Diponegoro Journal of Accounting, 2015)
Indonesia applies Self Assessment System for its tax collection system.This success depends on parties whether the fiscus or tax payers. This research aims to test factors influenced the application of Self Assessment System. This research uses tax payers obidience, tax payers knowledge, tax payers awareness, and service of fiscus as independent variable. As dependent variable, this research uses the application of Self Assessment Systemitself.This research uses survey method on tax payers which are entrepreneur in Semarang city. Samples are collected withquestionnaire on purposive Sampling. Then data are analyzed by multiple regression analysis.The result shows tax payers obidience, tax payers knowledge, tax payers awareness, and service of fiscus influence the application of Self Assessment System by 56,9%